Market Participation and Food Security Status of Bio-Fortified Cassava Processors in South Western Nigeria - Adetomiwa, Kolapo; Yusuf, Olayinka J; Abdulmumin, Muhammed Opeyemi (International Journal of Sustainable Agricultural Research, 2020)
A better understanding of the extent of food insecurity and its determinants, particularly among rural households, is a step towards proffering solutions to this menace. The study assessed market participation and food security status of bio-fortified cassava processors in South-Western Nigeria. A multistage sampling technique was used to source for data from 160 bio-fortified cassava processor through a well-structured questionnaire. Descriptive statistics, household commercialization index, Food Insecurity Experience-Based Measurement Scales-United States Department of Agriculture (FIEMS-USDA) and Multinomial Logistic Regression (MLR) were used to analyze the data. The result of the study showed that the mean age of the processors was 48(±11.36). Majority (70.6%) of the bio-fortified cassava processor had a high market participation level with a mean household market participation index of 63.14±7.23%. About (58.75%) of the respondents were food insecure with moderate hunger level. The result of the MLR showed that farm income, the value of processed bio-fortified cassava output, susceptibility to sickness, membership of association and access to extension services were significantly related to food insecurity status of the bio-fortified cassava processor. Appropriate programs and policy measures that would increase the value of the processed bio-fortified cassava output and farm income should be targeted towards the processors as this would help to reduce their dependency and increase the food security status of their households.